Kepemimpinan Kepala Sekolah dalam Meningkatkan Profesional Guru Di Era Revolusi 4.0 - Kalimatusyaro, Mei; Asmaul Husnah; Acmad Syaikhu ZA (Journal of Social Science and Economics, 2023)
How is the Principal's Leadership in Improving Teacher Professionalism in the 4.0 Revolution Era at the Empat Lima 1 Junior High School, Kedungpring Lamongan? What are the obstacles to the Principal's Leadership in Improving Teacher Professionalism in the 4.0 Revolution Era at the Empat Lima 1 Junior High School, Kedungpring Lamongan? What are the efforts of the Principal's Leadership in Improving Teacher Professionalism in the 4.0 Revolution Era at the Empat Lima 1 Junior High School, Kedungpring Lamongan? The approach used by researchers is a qualitative approach. It is called qualitative because the problems discussed in this study are not related to numbers, but describe, describe, and describe the leadership of school principals in improving teacher professionalism in the revolutionary era 4.0 (Case Study of Junior High School Empat Lima 1 Kedungpring Lamongan) as it is . Qualitative research is research that intends to understand phenomena about what is experienced by research subjects such as behavior, perceptions, motivations, actions, holistically, and in a descriptive way in the form of words and language, in a special natural context and by utilizing various scientific method (Lexy J. Moleong, 2012). With a qualitative approach, this research is expected to be able to reveal comprehensive facts about the leadership of school principals in increasing teacher professionalism in the revolutionary era 4.0 (Case Study of Junior High School Empat Lima 1 Kedungpring Lamongan). The type of research that researchers use is case study researchers. A case study is a comprehensive description and explanation of various aspects of an individual, group, organization, program, social situation and so on. Surachmad (1982) explained that a case study is an approach that focuses on a case intensively and in detail (Wayan Suwendra, 2018). While the case study model that researchers use is the case study model of Robert K. Yin. According to Robert K. Yin, case studies are more desirable to track contemporary events, if the events concerned cannot be manipulated. Because of this, case studies are based on the same techniques by adding two sources of evidence that are usually not included in the historian's options, namely observation and systematic interviews. Again, although case and historical studies may overlap, a unique strength of the case study is its ability to deal fully with a wide variety of types of documentary, equipment, interview, and observational evidence. Moreover, in some situations such as participant observation, informal manipulation can also occur.